Sociological and Aesthetic Aspects of Polish Symphonic Hip-hop. The Case of 2015 by Miuosh, Jimek and NOSPR - Kasperski, Jakub (Interdisciplinary Studies in Musicology, 2025)
In the middle of the second decade of the 21st century, Polish hip-hop saw a series of projects combining the genre with classical music in various ways: from classical arrangements, through symphonic rearrangements of existing repertoire, to original instrumental works. The author looks at this phenomenon, its genesis and development, focusing mainly on the 2015 project by Miuosh, Jimek and NOSPR, considered the most popular and influential among them. The analysis will be primarily sociomusicological, showing, on the one hand, how the categories of hip-hop and classical music were and are incompatible with each other in terms of social and aesthetic issues (which prevented their previous syntheses), and, on the other hand, how genre-normative listening situations were shaped during public presentations of the work.